Features of changes in anticoagulant hemostasis system in patients with hypertensive disease with concomitant hyperuricemia - Valigura, Maria (ScienceRise: Medical Science, 2018)
Aim of the research was to study the state of anticoagulant and fibrinolytic units of the hemostasis system in patients with hypertension associated with hyperuricemia. Materials and methods. We surveyed 133 people (80 male and 53 female), whose average age was 56.19±7.29 years, all patients were divided into 3 groups. The first main group was 54 patients with arterial hypertension with concomitant hyperuricemia, the second group was made up of 50 patients with hypertension and normal uric acid levels, and the third – 15 patients with hyperuricemia without increase in blood pressure, and the control group consisted of 14 practically healthy subjects comparable in age and sex. Hyperuricemia was determined at uric acid levels >7 mg/dL (>413 μmol/L). The activity of anticoagulant and fibrinolytic units of hemostasis was studied as a result of conducting of special laboratory tests: antithrombin III, protein C, plasminogen and XIIa-dependent fibrinolysis. Non-parametric statistical methods were used to analyze the data: U-Mann-Whitney, probable differences were considered at p<0.05. Results. In the examination of patients, we found suppression of the activity of antithrombin III, in the first group of patients, 23 % was large in terms of the control group, while the difference between the groups (in groups I and II) was 18.3 %. The protein C activity in the first group was reduced by 25.7 % compared with the control group and by 14.8 % less than that of group II. When comparing the parameters of the anticoagulating potential of blood groups among patients, it was determined that the level of antithrombin III was the lowest in patients with group I, namely 18.3 % when compared with group III (p <0.001) and 23.1 % when compared with II group (p <0.001). The protein C was the lowest in patients in group I by 14.8 % compared with group III (p <0.001) and by 25.7 % when compared with group II (p <0.001). Plasminogen (PG) was suppressed in all groups of patients: at hypertension by 16.7 % (p <0.01), with hyperuricemia by 32.1 % (p<0.001), with hypertension with concomitant hyperuricemia by 26.7 % (p<0.001). A significant increase in the activity of indicators of Hageman-dependent fibrinolysis was also found, in group I of patients with combined course of Hageman-dependent fibrinolysis, it was 3.5 times more (p<0.001), compared to the control group, in group II patients this indicator was 2.2 times more than in patients of the control group (p<0.001), and in group III patients 2.8 times (p<0.001). Conclusion. In hypertensive disease without concomitant hyperuricemia, AT III and protein C decreased, reflecting the anticoagulant potential of blood plasma, and in hypertensive patients associated with concomitant hyperuricemia, an even greater decrease in plasma hemostasis and prolonged fibrinolysis time was observed